Potresno utrjevanje zidanih stavb - predstavitev raziskav s kompoziti armiranih maltnih oblog - Boem, Ingrid (Gradbeni vestnik, 2023)
Over the last 20 years, Composite Reinforced Mortars (CRM) have gradually become widespread as innovative strengthening techniques for the seismic protection of existing masonry buildings. They combine an inorganic mortar layer, applied to the masonry surface, with a high tensile resistant, non-corrosive, fiber-based reinforcement. The paper traces the main steps of an in-depth research route on a specific CRM technique, providing an overview on the experimental testing and numerical modeling experiences aimed at achieving an in-depth knowledge on its behavior and on its effectiveness in improving masonry performance. It is an example of a systematic approach to research, which deals with the complexity and multiplicity of aspects that need to be considered by professional designer when choosing among the solutions available on the market.
Keywords: composites; eksperimenti; experimental tests; kompoziti; masonry strengthening; numerical modelling; numerično modeliranje; potresna odpornost; seismic vulnerability; utrjevanje zidanih stavb